Online Counseling Services: The Role of Opinion Leaders in Purchase Intentions - Marieta Vania Wellyan; Desak Nyoman Arista Retno Dewi (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2023)
The declining mental health condition due to the Covid-19 pandemic raises the need for counseling. The pandemic situation and the era of digitalization have encouraged the re-emergence of online counseling services know as e-counseling. The limitations of the online counseling process do not reduce consumers' intention to use this service. Intention to use e-counseling services can be determined by positive thoughts and perceptions of the information provided by individuals or organizations who have credibility and can be trusted (opinion leaders) regarding the quality of services offered. This study aims to analyze the relationship between the perception of opinion leaders and purchase intentions on e-counseling services. This research is a quantitative research with purposive sampling technique. Data from 101 research subjects were processed using Kendall's Tau B non-parametric statistics. A significant value of 0.000 (p <0.05) indicates there is a positive relationship between perceptions of opinion leaders and purchase intention with an effective contribution of 33.5%.Kondisi kesehatan mental yang menurun akibat pandemi Covid-19 memunculkan kebutuhan melakukan konseling. Situasi pandemi dan era digitalisasi mendorong munculnya kembali jasa konseling secara online yang dikenal dengan e-counseling. Keterbatasan proses konseling yang dilakukan secara online tidak menurunkan niat konsumen untuk menggunakan jasa ini (purchase intention). Niat menggunakan jasa konseling online dapat ditentukan oleh pemikiran dan persepsi yang positif atas informasi yang diberikan oleh individu atau organisasi yang memiliki kredibilitas dan dapat dipercaya (opinion leader) mengenai kualitas jasa yang ditawarkan. Penelitian ini bertujuan menganalisa hubungan persepsi terhadap opinion leader dan purchase intention pada jasa konseling online. Penelitian ini merupakan penelitian kuantitatif dengan teknik pengambilan sampel purposive sampling. Data dari 101 subyek penelitian diolah menggunakan statistik non-parametrik Kendall’s Tau B. Nilai signifikan sebesar 0,000 (p <0,05) menunjukkan ada hubungan positif antara persepsi terhadap opinion leader dan purchase intention dengan sumbangan efektif sebesar 33,5%.